Risk Factors Affecting Alternate Segregation in Blastocysts From Preimplantation Genetic Testing Cycles of Autosomal Reciprocal Translocations - Xie, Pingyuan; Hu, Liang; Peng, Yangqin; Tan, Yue-qiu; Luo, Keli; Gong, Fei; Lu, Guangxiu; Lin, Ge (Frontiers in Genetics, 2022)
Reciprocal translocations are the most common structural chromosome rearrangements and may be associated with reproductive problems. Therefore, the objective of this study was to analyze factors that can influence meiotic segregation patterns in blastocysts for reciprocal translocation carriers. Segregation patterns of quadrivalents in 10,846 blastocysts from 2,871 preimplantation genetic testing cycles of reciprocal translocation carriers were analyzed. The percentage of normal/balanced blastocysts was 34.3%, and 2:2 segregation was observed in 90.0% of the blastocysts. Increased TAR1 (ratio of translocated segment 1 over the chromosome arm) emerged as an independent protective factor associated with an increase in alternate segregation (p = 0.004). Female sex and involvement of an acrocentric chromosome (Acr-ch) were independent risk factors that reduced alternate segregation proportions (p < 0.001). Notably, a higher TAR1 reduced the proportion of adjacent-1 segregation (p < 0.001); a longer translocated segment and female sex increased the risk of adjacent-2 segregation (p = 0.009 and p < 0.001, respectively). Female sex and involvement of an Acr-ch enhanced the ratio of 3:1 segregation (p < 0.001 and p = 0.012, respectively). In conclusion, autosomal reciprocal translocation carriers have reduced proportions of alternate segregation in blastocysts upon the involvement of an Acr-ch, female sex, and lower TAR1. These results may facilitate more appropriate genetic counseling for couples with autosomal reciprocal translocation regarding their chances of producing normal/balanced blastocysts.